2003
DOI: 10.1007/s00422-003-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequence, time, or state representation: how does the motor control system adapt to variable environments?

Abstract: Does the observation of well-timed movements imply the existence of some internal representation of time, such as a hypothetical neural clock? Here we report the results of experiments designed to investigate whether subjects form a correct adaptive representation of mechanical environments that change in a very predictable manner. In these experiments, subjects were asked to execute arm movements over a twodimensional workspace while experiencing time-dependent disturbing forces. We provide a formal definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…As initially mentioned, several previous studies demonstrated motor memory interference when two different tasks were learned using the same arm [17,18,2125,32]. In some cases, this interference was shown to be reduced when associating the competing tasks with visual or proprioceptive context cues [3337].…”
Section: Discussionmentioning
confidence: 95%
“…As initially mentioned, several previous studies demonstrated motor memory interference when two different tasks were learned using the same arm [17,18,2125,32]. In some cases, this interference was shown to be reduced when associating the competing tasks with visual or proprioceptive context cues [3337].…”
Section: Discussionmentioning
confidence: 95%
“…For motor recovery, training on a variety of tasks provides better improvement in overall function than repetitions of the same task [7], [8]. Rather than rote memorization of motor commands, the nervous system appears to learn associations between forces and movement states [18]. Allowing free movement presumably would provide the richest experiences of these dynamic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that the motor system more successfully generalizes learned motor plans between movements spanning similar positions and velocities [16], and exhibits a preference for such generalization in a joint-based coordinate frame [17]. Evidence suggests that the motor system plans according to associations between expected forces and movement states [18]. Furthermore, the motor system has been shown to transfer skills between environments with overlapping characteristics [19]–[21].…”
Section: Introductionmentioning
confidence: 99%
“…The motor system can generalize learned strategies to various movement trajectories spanning similar positions and velocities [29]. Rather than rote memorization of motor commands, the nervous system appears to learn associations between forces and movement states[30]. From a systems modeling perspective, broader excitation of movement states informs more accurate system identification [31].…”
Section: Discussionmentioning
confidence: 99%